2018
DOI: 10.1016/s1569-9056(18)31118-7
|View full text |Cite
|
Sign up to set email alerts
|

Decision aids for prostate cancer screening choice: A systematic review and meta-analysis

Abstract: IMPORTANCE US guidelines recommend that physicians engage in shared decision-making with men considering prostate cancer screening. OBJECTIVE To estimate the association of decision aids with decisional outcomes in prostate cancer screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 1 publication
2
30
0
2
Order By: Relevance
“…Hälleberg-Nyman et al [16] in qualitative study reported patient-reported satisfaction scores to be better in patients receiving radiotherapy, when clinical consults were supplemented with the interactive app, Interaktor, corroborating the aforementioned view. In prostate cancer, SDM with DAs is particularly pertinent, due to controversies in areas such as prostate cancer screening and the availability of plethora of therapeutic options [31]. In this review, a number of PCAs addressed the subject of PSA screening and reassuringly most PCAs had a neutral tone for PSA screening.…”
Section: Individual Applications Includes Studies Evaluated By the Aumentioning
confidence: 97%
“…Hälleberg-Nyman et al [16] in qualitative study reported patient-reported satisfaction scores to be better in patients receiving radiotherapy, when clinical consults were supplemented with the interactive app, Interaktor, corroborating the aforementioned view. In prostate cancer, SDM with DAs is particularly pertinent, due to controversies in areas such as prostate cancer screening and the availability of plethora of therapeutic options [31]. In this review, a number of PCAs addressed the subject of PSA screening and reassuringly most PCAs had a neutral tone for PSA screening.…”
Section: Individual Applications Includes Studies Evaluated By the Aumentioning
confidence: 97%
“…These data construct important parts prepared to publication after comparison analysis. Except these, reassessment on feedback data also help us conduct better medical training for our doctors and researchers 8,11 .…”
Section: Analysis Based On Educational Intervention and Patient Feedbackmentioning
confidence: 99%
“…Some of patients are admitted to hospital for further operation treatment, radiotherapy or chemotherapy based on abovementioned assessment, of which the clinical information about basic characteristics and examination indexes are recorded in medical records 7,8 . Some of patients are only follow-up in outpatient department and subjected to watchful waiting, active surveillance or drug therapy.…”
Section: Management On Clinical Samplementioning
confidence: 99%
“…However, not all prostate cancer decision aids are created equal, and many are subject to bias. Ironically and paradoxically, a pooled analysis of 19 randomized studies showed no difference in the decision to undergo screening whether a decision aid was used but did show a small decrease in decisional conflict …”
Section: Type Of Bias Potentially Affecting Men and Physicians Regardmentioning
confidence: 99%